Efektivitas dan Keamanan Beraprost untuk Pengobatan Klaudikasio Intermiten pada Critical Limb Threatening Ischemia (CLTI) - Pangestu, Andhika; Asicha, Nur; Cahyanur, Rahmat; Resultanti, Resultanti (Jurnal Penyakit Dalam Indonesia, 2023)
Critical limb threatening ischemia (CLTI) is the most advanced stage of peripheral arterial diseases. Alternative treatment for claudication in CLTI patients is beraprost. We aim to review effectiveness and safety beraprost for relieve symptoms in CLTI. We conducted systematic literature searching using PubMed/MEDLINE, Embase, ProQuest, and Cochrane databases. Selected articles were examined for duplication and screened by abstract and title. Then, we appraised the articles based on the critical appraisal sheet from Centre for Evidence-Based Medicine (CEBM) University of Oxford. We found one systematic review-meta analysis (SR-MA) which involved 4,477 randomized participants. The results from this study are moderate quality evidence that prostanoids reduced rest pain (RR 1.30; 95%CI 1.06 – 1.59) and promoted ulcer healing (RR 1.24; 95%CI 1.04 – 1.48). In adult patients with CLTI and intermittent claudication as the primary complaint, vasodilator agents such as beraprost have a beneficial effect and a favorable therapeutic response. Numerous effects, including cardiovascular benefit, adverse events, resting pain relief, ulcer healing, outcome maximum walking distance (MWD), and pain-free walking distance, demonstrate the benefit (PFWD). The benefits of beraprost differ depending on the mechanism of action and pharmacokinetics of the drugs.